2013
DOI: 10.1037/a0030398
|View full text |Cite
|
Sign up to set email alerts
|

Two ways to the top: Evidence that dominance and prestige are distinct yet viable avenues to social rank and influence.

Abstract: The pursuit of social rank is a recurrent and pervasive challenge faced by individuals in all human societies. Yet, the precise means through which individuals compete for social standing remains unclear. In 2 studies, we investigated the impact of 2 fundamental strategies-Dominance (the use of force and intimidation to induce fear) and Prestige (the sharing of expertise or know-how to gain respect)-on the attainment of social rank, which we conceptualized as the acquisition of (a) perceived influence over oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

55
1,181
9
12

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 859 publications
(1,257 citation statements)
references
References 205 publications
(356 reference statements)
55
1,181
9
12
Order By: Relevance
“…Previous research has shown that priming high rank improves performance in social-evaluative situations such as mock job interviews, which leads to better outcomes (e.g., being hired for the job) (15,16). These positive social evaluations are influenced by status-relevant behaviors such as competence, dominance, and warmth (17,18). Again, however, the causal effect of status on performance in social-evaluative settings has only been tested in stable hierarchies.…”
Section: Significancementioning
confidence: 98%
See 2 more Smart Citations
“…Previous research has shown that priming high rank improves performance in social-evaluative situations such as mock job interviews, which leads to better outcomes (e.g., being hired for the job) (15,16). These positive social evaluations are influenced by status-relevant behaviors such as competence, dominance, and warmth (17,18). Again, however, the causal effect of status on performance in social-evaluative settings has only been tested in stable hierarchies.…”
Section: Significancementioning
confidence: 98%
“…Status, which is also referred to as prestige, can be defined as social standing that is granted to individuals for superior skills, success, or knowledge (18). Power is defined as asymmetrical control over resources and tends to be positively correlated with status in realworld hierarchies (36,37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social status can be defined as relative access to contested resources within a group, particularly the deference or admiration of group members (2,3). To gain status, individuals attempt to influence perceptions of their dominance (i.e., ability to inflict costs on others) or prestige (i.e., ability to confer benefits on others) (3,4). Dominance and prestige can be difficult to disentangle because dominance can be a source of prestige and vice versa (5).…”
mentioning
confidence: 99%
“…Such inferences are essential for successful social communication, as they determine what kind of strategies we use to interact with other people and even whether to continue the interaction. For example, if we perceive a person as friendly, we are more likely to help them when they are in trouble; if we perceive someone as dominant and aggressive, we are less likely to choose them as a group member to work on a collaborative project; and if we perceive a person as being trustworthy, we are more inclined to cooperate with them (Cheng, Tracy, Foulsham, Kingstone, & Henrich, 2013;Clark, Pataki, & Carver, 1996;Krumhuber, Manstead, Cosker, et al, 2007;Van Kleef, De Dreu, & Manstead, 2010).…”
mentioning
confidence: 99%